Alternative medicine: cost and subjective benefit in rheumatoid arthritis. Issue 6355 (4th December 1982) - Pullar, T; Capell, H A; Millar, A; Brooks, R G
Abstract : Seventy-eight patients with seropositive rheumatoid arthritis were asked about money spent in an attempt to help their arthritis. This included expenditure on alternative medicine, aids for the home, and conventional medicine. Most money was spent on, and most benefit was derived from, aids for the home. Sixty per cent of the patients had tried alternative medicine, but expenditure on this was relatively low and only a small proportion found it helpful.